\log_{7} (2x - 4)" alt="\log_{7} (4x - 6) > \log_{7} (2x - 4)" align="absmiddle" class="latex-formula">
Данное неравенство равносильно системе:
0 \ \ \ \ \ \ \ \\2x - 4 > 0 \ \ \ \ \ \ \ \\4x - 6 > 2x - 4\end{array}\right" alt="\left\{\begin{array}{ccc}4x - 6 > 0 \ \ \ \ \ \ \ \\2x - 4 > 0 \ \ \ \ \ \ \ \\4x - 6 > 2x - 4\end{array}\right" align="absmiddle" class="latex-formula">
\dfrac{3}{2} \\x > 2\\x > 1\end{array}\right" alt="\left\{\begin{array}{ccc}x > \dfrac{3}{2} \\x > 2\\x > 1\end{array}\right" align="absmiddle" class="latex-formula">
Общим решением будет интервал ![x \in (2; +\infty) x \in (2; +\infty)](https://tex.z-dn.net/?f=x%20%5Cin%20%282%3B%20%2B%5Cinfty%29)
Ответ: ![x \in (2; +\infty) x \in (2; +\infty)](https://tex.z-dn.net/?f=x%20%5Cin%20%282%3B%20%2B%5Cinfty%29)